Combined effects of geometric and material non-linearities on one dimensional structural members - Ramaraju, Ramgopal Varma; Rao, G. Venkateswazra (Penerbit Universiti Malaysia Pahang, 2014)
Combined effects of geometric and material nonlinearities on a uniform column subjected to an axial compressive load are presented in the present note. A simple, direct iterative numerical method has been proposed to study the geometric and material non-linear behavior of columns subjected to varying boundary conditions. Introduction of material non-linearity in the large deflection analysis of columns subjected to an axilll compressive load reveals a reduction in Euler stress obtained when compared to the effect of geometric non-linear analysis and increase in the same when compared to the effect of material non-linear analysis. A convergence study has been carried out for the results obtained from the proposed iterative method to prove the efficacy.